The Level of Awareness of Fake Dental Veneers Among Dental and Non-Dental Students Studying in Malaysia: A Cross-Sectional Study - Usman, Jafar Abdulla Mohamed; Kung , Kah Heng; Tieu , Shen Huong; Aidil Fithri, Farah Najwa Binti (International Journal of Dental Materials, 2026)
Background: Lately, there has been an increase in the placement of fake veneers by unregistered individuals without a license from the Malaysian Dental Council.Aim: To determine the level of awareness of fake veneers among MAHSA University dental students and non-dental students.Materials and methods: A cross-sectional study was conducted involving 350 dental and non-dental students in MAHSA University. Self-administered questionnaires were distributed to the students. The data were then analyzed using an independent t-test to determine the level of awareness of fake veneers among dental and non-dental students.Results: Among 350 participants, 147 were dental (42%) and 203 non-dental students (58%), with a mean age of 22.69 ± 1.68. There was a significant mean difference between the level of awareness of fake veneers among dental students and non-dental students (p